Plasmodial Transcription Factors and Chromatin Modifiers as Drug Targets - Luisa Fernanda Ortega Sepulveda; Gabriela Mendes de Oliveira; Elaine Hellen Nunes Chagas; Nele Wild; Franciarli Silva da Paz; Carsten Wrenger; Gerhard Wunderlich (MDPI AG, 2023)
The complex life cycle of the malaria parasite Plasmodium requires the parasite to adequately adapt to different conditions. For this reason, Plasmodium strictly controls its gene expression, and given its evolutionary distance from the human host, the involved factors may figure as attractive potential drug targets. In recent years, several unique transcription factors and chromatin modifiers have been identified and partially characterized in Plasmodium falciparum and in the murine species P. yoelii and P. berghei. This review unites data from studies focusing on drug development against enigmatic plant-like AP2-transcription factors and chromatin modifiers, such as histone acetyl transferases and deacetylases and histone methyltransferases and demethylases. Considering the reported success of inhibition of both factors, these may be included as targets to effectively combat the parasite by perturbing its control of gene expression.